2018
DOI: 10.3892/mmr.2018.8446
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor trichostatin A and autophagy inhibitor chloroquine synergistically exert anti-tumor activity in H-ras transformed breast epithelial cells

Abstract: Histone deacetylase inhibitors (HDACIs) cause oncogene-transformed mammalian cell death. Our previous study indicated that HDACIs activate forkhead box O1 (FOXO1) and induce autophagy in liver and colon cancer cells. However, whether FOXO1 is involved in HDACI-mediated oncogene-transformed mammalian cell death remains unclear. In the present study, H-ras transformed MCF10A cells were used to investigate the role of FOXO1 in this pathway. Results showed that trichostatin A (TSA), a HDACI, activated apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
0
22
0
2
Order By: Relevance
“…It had been previously described that the use of autophagy inhibitors, such as CQ, with drugs that induces autophagy, such as HDACi, enhanced the cytotoxic response of these drugs [ [18] , [19] , [20] , [21] , [22] , [23] , 48 ]. Therefore, we hypothesized that the synergistic effect obtained after CQ/LBH cotreatment could also be due, at least in part, to an inhibition of the prosurvival autophagy pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It had been previously described that the use of autophagy inhibitors, such as CQ, with drugs that induces autophagy, such as HDACi, enhanced the cytotoxic response of these drugs [ [18] , [19] , [20] , [21] , [22] , [23] , 48 ]. Therefore, we hypothesized that the synergistic effect obtained after CQ/LBH cotreatment could also be due, at least in part, to an inhibition of the prosurvival autophagy pathway.…”
Section: Resultsmentioning
confidence: 99%
“…HDACi also promote autophagy, but this effect instead of exerting antitumor effects has been proposed as a potential mechanism of resistance to these drugs; autophagy might recycle proteins to generate energy in an attempt to survive stressful conditions generated by the treatment [17] . This is the reason why some researchers have analyzed the effect of the combination of HDACi and other proautophagy drugs with autophagy inhibitors, such as Chloroquine (CQ), and have found synergistic effects in some tumor cell lines, such as breast, colon, leukemic and neuroblastoma cell lines [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The current data suggest a model in which unmodi ed, full-length APE1 is mainly targeted to the nucleus via its N-terminal elements [3]. More importantly, APE1 is widely overexpressed in most tumor tissues, and APE1 overexpression is associated with poor prognosis, chemoresistance or radioresistance, and increased angiogenesis [4][5][6]. In this study, cytoplasmic APE1 may mediate resistance to cisplatin in lung cancer, and upregulation of cytoplasmic APE1 induced by plasmid transfection increased resistance to cisplatin.…”
Section: Introductionmentioning
confidence: 55%
“…Our data showed that breast cancer cells undergo cytoprotective autophagy in response to HNK treatment suggesting that combining HNK with an autophagy inhibitor can potentially yield increased inhibition of breast tumor growth. Autophagy inhibitor, chloroquine has been shown to increase drug efficacy in preclinical studies 39,40 . We first determined whether the interaction between HNK and CQ is additive, synergistic or antagonistic in nature using Compusyn software (Compusyn Inc., Paramus, NJ, USA).…”
Section: Concomitant Treatment With Autophagy Inhibitor and Hnk Synermentioning
confidence: 99%